Radical Strategy for the Transition-Metal-Catalyzed Synthesis of γ-Lactones: A Review - Wei, Bin; Li, Ke-Wei; Wu, Yan-Chen; Tong, Shi-Qi; Song, Ren-Jie (Synthesis, 2020)
The γ-lactone skeleton is very important component of various natural products, biological molecules, food additives, and perfumes. As a result, much effort has been made towards such compounds. In this review, we summarize recent progress in transition-metal-catalyzed annulation reactions for the formation of γ-lactone derivatives through a radical pathway. Various reagents, such as anhydrides, Togni’s reagent, TMSN3, arenesulfonyl chlorides, arenediazonium salts, dibenzoyl peroxides, O-benzoylhydroxylamine, NFSI, and α-halocarboxylic compounds, used in radical cyclization reactions are described, and the mechanisms of these radical annulation reactions are also discussed.1 Introduction2 Annulations of Alkenes with Anhydrides3 Annulations of Unsaturated Carboxylic Acids with Nucleophiles4 Annulations of Alkenes with α-Halocarboxylic Compounds5 Conclusions and Outlook
Keywords: transition metals; oxidation; radical reactions; annulations; γ-lactones; tetrahydrofuran-2-ones